2021
DOI: 10.2991/assehr.k.211228.061
|View full text |Cite
|
Sign up to set email alerts
|

Elaborating Visual Narrative into Modern Adaptation Concept for Picture Book with Indonesian Folklore Theme

Abstract: Folklore shows how a culture brings its point of view and values. It is also an agent of social values such as honesty, kindness, forgiveness, and many more. Through picture book, message from folklore can lead children understanding their society. These aspects are reasons why folklore becomes a favourite genre in picture book. Hence, some argue that folklore also store up cruelty and intimidating content which are not suitable for children. This leads creator and publisher to keep up with new way of adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Visualization of those scenes often portrayed using middle or high-level metaphor (Indrayati et al, 2018). Therefore, as Ratri et al (2021) stated, in order to effectively teach complex subjects in folklore to Indonesian children, a formula of reduction, simplification, removal of sensitive content, and narrative construction from the perspective of the child is required. Although the subject of folklore was not specifically discussed but rather a small part of the samples, this study found similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of those scenes often portrayed using middle or high-level metaphor (Indrayati et al, 2018). Therefore, as Ratri et al (2021) stated, in order to effectively teach complex subjects in folklore to Indonesian children, a formula of reduction, simplification, removal of sensitive content, and narrative construction from the perspective of the child is required. Although the subject of folklore was not specifically discussed but rather a small part of the samples, this study found similar conclusions.…”
Section: Discussionmentioning
confidence: 99%